Discovery of the first wild population of the small red brocket deer Mazama bororo (Artiodactyla: Cervidae) - Vogliotti, Alexandre [UNESP]; Duarte, José M. B. [UNESP] (My University, 2009)
Mazama bororo was described from a few captive specimens in Brazil by cytogenetic and morphological characters. These specimens supposedly originated in the Southern Atlantic Forest; however, no wild population has been reported. This study was initiated in 1998 to investigate the presence of this species in forest remnants of the Paranapiacaba mountain range, south São Paulo State, Brazil. Five specimens were captured between 2000 and 2002. Cytogenetic analysis from blood samples confirmed its specific identification, documenting the first population of small red brocket deer at the Intervales State Park. © SAREM, 2009.
Keywords: Atlantic forest; Brazil; Cryptic deer species; Cytogenetics; Neotropical fauna